1988
DOI: 10.1001/archotol.1988.01860140084027
|View full text |Cite
|
Sign up to set email alerts
|

Pigmentation, Anesthesia, Behavioral Factors, and Salicylate Uptake

Abstract: \s=b\In four experiments, 54 pigmented rats were used to examine the time course of sodium salicylate uptake in serum, cerebrospinal fluid, and perilymph. Subjects were tested under sodium pentobarbital anesthesia or while conscious. Compared with previously reported data from albino rats, pigmented subjects generally showed increased salicylate uptake. Moreover, the data suggested two different, time-dependent clearance mechanisms in conscious animals not observed in anesthetized rats.Daily injections of sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…SEM = 1.4. These levels were in agreement with expectations based on peak salicylate levels obtained from adult rats 2-3 h after injection (Jastreboff, Issing. et al, 1988) and within the range observed in humans treated with salicylate (Mongan, Kelly.…”
Section: Methodssupporting
confidence: 92%
See 2 more Smart Citations
“…SEM = 1.4. These levels were in agreement with expectations based on peak salicylate levels obtained from adult rats 2-3 h after injection (Jastreboff, Issing. et al, 1988) and within the range observed in humans treated with salicylate (Mongan, Kelly.…”
Section: Methodssupporting
confidence: 92%
“…In adult rats, there is no evident of long-term cumulative salicylate effects (Jastreboff, Hansen, Sasaki, & Sasaki, 1986;. Salicylate uptake in serum, cerebrospinal fluid, and perilymph reaches a maximum level in conscious, active adult rats about 2 h after injection, and salicylate levels tend to have a half life of about 6 h (Jastreboff, Issing, et al, 1988). Although we did not suspect that multiple injection effects would be different in preweanling pups, we nevertheless conducted an examination to determine whether chronic salicylate injections might have a cumulative effect on the behavior of young rats.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In more recent work, we have shown that 1.4 mM of sodium salicylate causes significant loss of SGN in cochlear cultures; cell loss is preceded by soma shrinkage, a morphological feature of apoptosis, and caspase activation (Wei, 2009). The 1.4 mM dose used in our culture is clinically relevant since it is similar to the concentration seen in the cerebrospinal fluid and perilymph of animals that develop salicylate-induced tinnitus and hearing loss (Jastreboff et al , 1986; Jastreboff et al , 1988b). Our results plus previous in vitro studies suggest that further studies are needed to determine if high-dose, long term salicylate treatment damages SGN.…”
Section: Discussionmentioning
confidence: 99%
“…90 minutes after an i.p. injection of 350 mg/kg sodium salicylate (corresponding to 300 mg/kg salicylic acid), the salicylate serum level in the rat was 625 mg/L [106]. For the dosage of 100 mg/kg inducing reliable tinnitus in the rat, the expected salicylate serum concentration is approiamtely 56 mg/L.…”
Section: Established Ways Of Tinnitus Induction In Animal Researchmentioning
confidence: 99%